Analysis the effect of variable wind speed on roof trusses of residential building using ms 1553 : 2002 - Norain, Mohd Sabri (2014)
Wind is a natural phenomenon that occurs in all regions and can be predicted. But nowadays, Malaysia experienced an extreme climate change and unexpected wind condition which is lead to severe damage to the building especially residential building and this case had increase in past few years. As this problem is forecasted to lead to the great amount of losses in term of money and can cause injuries to people, this paper is provide to study the characteristic of wind and to determine the maximum wind speed that can cause failure to roof, and hence provide theguideline of the safety design of roof truss for residential building. The research is focuses on standard roof trusses design of residential building with JKR standard as a guideline. As referring to the postdisaster investigation of major windstorm events that had been conducted in Unites States for past two decades prove that the failure of the roof structure is obviously because of the poor construction of the truss system and due to the construction itself that not following code. Based on the past research also shown that the presence of wind load in term of suction and uplift force that normally ignored in construction is the main cause of roof system to fail. The research is proceed by using data of various wind speed that lead to different potential damage to the building which is Fujita Scale and Tamura Scale. Basic wind speed of 33.5 m/s is set up as a benchmark in determining the standard size of the truss and the dimension of the truss itself. The value of wind speed from Tamura Scale is used in analysing the loading on the roof truss by using simplified procedure in MS 1553:2002 since the cases is investigated in Malaysia. The methodology of the research then projected by create a model of roof trusses in ANSYS. Civi1FEM where the roof truss is modelled using hot rolled cross section with the same truss span, truss spacing, purlin spacing as calculated using simplified procedure. At the end of the research, it found that the minimum size of truss that can support basic wind speed 33.5mIs is 75 x 75 x 8 and truss to fail when reach wind speed 140mls when considering wind tunnel coefficient and 1 60m/s without considering wind tunnel coefficient. As a nutshell, this can be conclude that in designing for roof trusses, the value of wind speed that should be considered in the design is not only focusing on basic wind speed but also increase the design capacity of the trusses so that when unexpected high wind speed occur, the roof truss still can support the load without any failure.